Efeitos do treinamento aeróbio intervalado de alta intensidade e contínuo de moderada intensidade sobre indicadores de saúde em escolares com obesidade central - Guilherme, Flávio Ricardo (2017)
To compare the effects of two aerobic training programs - a high intensity interval training (HIIT) and a moderate intensity continuous training (MICT) ? on health indicators from scholars with central obese. This is a randomized clinical trial, structured in 16 weeks of aerobic training. The sample was composed by 42 scholars (10 to 18 years old), from both sexes, randomized in two groups: HIIT program (HIITG, n = 22) and a MICT program (MICTG, n = 20). After 16 weeks of training (3 sessions/week), 34 adolescents finished the program (HIITG, n = 21; MICTG, n = 13). The HIITG group performed different models of interval training, progressively organized, and the MICTG trained in a fixed intensity from 60 to 80% of HRmax. Anthropometrical outcomes (Body Mass Index [BMI], Waist Circumference [WC], Height Waist Ratio [HWR], Body Fat Percentage [%BF]), cardiorespiratory fitness (CRF), blood pressure (systolic and diastolic) and metabolic profile (fasting blood glucose [FBG] , high density lipoproteins [HDL-C], low density lipoproteins [LDL-C], total cholesterol, non HDL cholesterol and triglycerides [TG]) were analyzed in baseline, after 8th and 16th week. Sixteen weeks of aerobic training resulted in significant reductions on both groups in BMI (HIITG = -4.5%, ES = -0.26 vs MICTG = -3.9%, ES = -0,24), WC (HIITG = -6.9%, ES = -0.64 vs MICTG = -6.6%, ES = -0.61), HWR (HIITG = -10.5%, ES = -1.00 vs MICTG = -5.2%, ES = -0.50), %BF (HIITG = -14.3%, ES = -0.59 vs MICTG = -9.8%, ES = -0.40), FBG (HIITG = - 6.1%, ES = -0.65 vs MICTG = -11.1%, ES = -0.89) and non HDL cholesterol (HIITG = -14.5%, ES = -0.44 vs MICTG = -11.0%, ES = -0.37), and increased CRF (HIITG = 15.2%, ES = 0.85 vs MICTG = 12.8%, ES = 0.71). Only HIITG statistically improved diastolic blood pressure (-17.0%, ES=-0.87), LDL-C (-13.3%, ES= -0.34) and total cholesterol (-11.9%, ES = -0.47), but only MICTG changed positively TG (-23.4%, ES = -0.44). No significant changes were observed for systolic blood pressure and HDLC. No differences were found in all variables between groups. Relating to inadequacy cases, both groups significantly changed TG, but only HIITG decreased significantly the number of adolescents in inadequacy from CRF and blood pressure. For the other variables, no significant changes were observed. Regarding the cases of inadequacy, both groups statistically altered TG, and only GIAI significantly decreased the number of adolescents with inadequacy for ACR and blood pressure. For the other variables, no significant changes were identified over time 16 weeks of HIIT or MICT positively impact health indicators (anthropometrical variables, metabolic profile and CRF) in obese adolescents, however, for the most effective changes in inadequacy cases, a period of intervention is needed